THE LEGAL EFFICACY OF STRATEGIES FOR PROTECTING CULTURAL HERITAGE AND PREVENTING ART CRIMES - Vashishtha, Namita; Singh, Shourie Anand (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cultural heritage of a country is its identity, and it is unique to a particular group or to that particular community. It surely reflects upon the lifestyle the language and the way of life of that nation. Such is the richness of cultural heritage that it can be tangible like a monument, or an artefact and it can be intangible like the cultural beliefs, the traditions, the rituals, the festivals and the practices of a particular country. The tangible cultural heritage can be immovable like the Taj Mahal of India, the Eiffel Tower of Paris, the Colosseum of Italy, the Stone Henge, Machu Picchu and many others. It is a known fact that cultural heritage of a place shapes a nation, it shapes the society for ages and prepares the future generations to come. The threat to any cultural heritage originates from the conflicting ideas or interest of other groups outside of a particular community, race or a nation. Sometimes the Heritage of a country has natural or manufactured objects which represent the Heritage significance of that time, era, group, race, community or belief. These objects whether natural or manufactured are also apart of cultural heritage.